(3Wi GddSGf aj CMGOjK GdWjdSGfs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg Wi GddSGf ai CMGOjK GdWjdSGf QLhJ Hg fTQ GdSfI GdfHhjI hGdBKGQ GdeUWahjI s
(3BNQgG (B:s
(3Yf GdabQ GdPi JRGjO MOg hCTGQg HbOhg GHf fHGJg Edi bhdg RQbI LSei hHjGV KdLgG GdCHdb ai aUd GdTJGA s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
Keywords: (3GdMOjK h GdeUWdMs